Impact of COVID-19 on community medicine education and training-postgraduates’ perspective: a qualitative exploration - Lakshmi, Makineedi Rama; Bhimarasetty, Devi Madhavi; Phani Madhavi, K. V. (International Journal Of Community Medicine And Public Health, 2023)
Background: World Health Organization on March 11, 2020 announced, the coronavirus disease 2019 (COVID-19) as pandemic. It has affected nearly every nation with remarkable alterations on everyday life. COVID-19 has had heartfelt impact on the medical education worldwide. Closure of the medical schools and universities has disturbed the education of future health professionals. During this pandemic, most educational institutions have opted for online education to protect their students. Online education has been gaining encouragement in almost all countries around the world. This coincides with the recently introduced competency-based medical education in India which has adopted online education. This created a new challenge for the institutions involved, the instructors and the students since they must adapt quickly to this new mode of learning. Methods: A Qualitative approach using Systematic methods (Free listing and Pile sorting) was done among postgraduate students during the month of September 2021. A total of 32 postgraduates were included in the study. Results: A total of 32 postgraduates were included. Among them 23 (72%) were females and 9 (28%) were males. According to salience score, effects of COVID on medical education in postgraduates’ perspective in decreasing order are loss of academics, reduced clinical exposure, less student teacher interaction. One positive effect is new era of E-learning. Pile sorting resulted into two piles academic loss and technical issues. Conclusion: COVID-19 has created a lot of impact on medical education creating psychological stress more due to online education and academics are hampered due to COVID duties.